Antifeedant, cytotoxic, and anti-inflammatory neo-clerodane diterpenoids in the peltate glandular trichomes and fresh leaves of Ajuga forrestii. (June 2021) - Wang, Ying; Liu, Yan-Chun; Li, Wen-Yuan; Guo, Kai; Liu, Yan; Li, Sheng-Hong
Abstract: The Lamiaceae plant Ajuga forrestii Diels is a traditional Chinese herbal medicine with abundant glandular trichomes (GTs), but their chemistry and biological functions remain uninvestigated. Here, a panel of six highly functionalized neo -clerodane diterpenoids was localized to the peltate GTs of A. forrestii using laser microdissection coupled with HPLC analysis, indicating that the GTs of A. forrestii are an excellent material for the elucidation of the yet unclear biosynthetic pathway of natural neo -clerodane diterpenoids. In addition, four undescribed neo -clerodane diterpenoids with an acyclic C-9 side chain including two pairs of 1:1 mixture of inseparable diastereomers, ajuforrestins D-G, were isolated from the fresh leaves of A. forrestii together with six known compounds. The structures of the undescribed compounds were elucidated by spectroscopic (including 1D and 2D NMR and HR-ESI-MS) analyses. Biological assays indicated that the major GT compound ajugacumbin B and undescribed ajuforrestins D/E showed antifeedant activity against Helicoverpa armigera, suggesting that neo -clerodanes in A. forrestii should be involved in plant defence against insects. Moreover, the abietane diterpenoid ajuforrestin B exhibited significant anti-inflammatory activity on the secretion of interleukin-2 (IL-2) and cytotoxicity against three cancer cell lines, NCI-H1975, HepG2 and MCF-7, suggesting that ajuforrestin B could positively contribute to the therapeutic effects of this traditional Chinese medicine. Graphical abstract: Image 1 Highlights: Six diterpenoids were localized to the glandular trichomes of Ajuga forrestii Diels. Four diterpenoids from the whole leaves were undescribed. Ajugacumbin B and undescribed ajuforrestins D/E exhibited antifeedant activity. Ajuforrestin B showed significant anti-inflammatory and cytotoxic activities.